PEMBERDAYAAN IBU HAMIL DALAM DETEKSI DINI KEHAMILAN RESIKO TINGGI DI PMB BASHORI SURABAYA - Nur Masruroh; Yati Isnaini Safitri (Community Development Journal, 2020)
This community service activity was carried out to increase the knowledge and understanding of high risk early detection of pregnancy at the Surabaya Bashori PMB. Time for the implementation of activities with a period of 3 months. The method provided is to provide knowledge about early detection of high-risk pregnancies. Counseling uses lecture and question and answer methods. Knowledge of pregnant women about high-risk pregnancies is measured by giving a pre-test in the form of a questionnaire filled out by mothers to determine the level of knowledge regarding high-risk pregnancy early detection conducted before counseling begins. After counseling, the mother was given the same questionnaire to measure the increase in her knowledge. The results of giving community service showed an increase in knowledge about high-risk pregnancies in pregnant women who had previously increased 40% to 77%. Active participation from pregnant women and the community is needed to conduct high-risk early detection of pregnancy.